Climate Change and Marine Fisheries in Africa : Assessing Vulnerability and Strengthening Adaptation Capacity - World Bank (World Bank, Washington, DC, 2020)
The understanding of the impacts of climate change on fisheries is constantly increasing and can be organized around several main factors - ocean acidification, sea-level rise, higher water temperatures, deoxygenation, changes in ocean currents - although these factors are unequally known and hard to model in terms of scope - where they will occur and where they will be felt the most - and severity. For instance, although the impacts of acidification are not as well understood as the effects of the other impacts, and are more difficult to measure, it is likely that they are more severe and widespread, particularly on shell-forming species, invertebrates, and coral associated species and throughout any carbon-dependent ecological processes. This report aims to assess, to the extent possible, the potential impact of climate change on fisheries and the related well-being of coastal African countries. It focuses on how the observed and anticipated ecological impacts of climate change are likely to affect fish stocks and the fisheries that depend on them and highlights the coastal countries and regions in Africa that are most vulnerable to climate change. Based on these projections, the report further assesses subsequent socioeconomic impacts on coastal countries and communities. The report concludes with a discussion of lessons learned from the modeling results.